2012
DOI: 10.1080/1745039x.2012.672220
|View full text |Cite
|
Sign up to set email alerts
|

Highly deoxynivalenol contaminated oats and immune function in horses

Abstract: The aim of the present study was to investigate the impact of deoxynivalenol (DON) on cellular and humoral immune parameters in horses. A feeding trial using naturally contaminated oats with high (20.2 mg/kg) and low (0.49 mg/kg) levels of DON was conducted. Two groups of five mares were fed 2 kg oats daily with high or low DON levels for two weeks, using a crossover design with a three-week wash-out period. No adverse effects on general health were observed. Only minor diet-related changes in differential blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 41 publications
2
9
0
1
Order By: Relevance
“…DON is a potent protein synthesis inhibitor (Rotter et al 1996), and the liver represents one of the target tissues. In agreement with Raymond et al (2003Raymond et al ( , 2005 and Khol-Parisini et al (2012), we observed no adverse effects between the different DON dosages in serum total protein, serum globulins and serum albumin (Tables 4 and 5). However, Johnson et al (1997) found a decrease in serum total protein, serum globulins and serum albumin concentrations in DON-exposed horses that may have been related to impaired liver metabolism.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…DON is a potent protein synthesis inhibitor (Rotter et al 1996), and the liver represents one of the target tissues. In agreement with Raymond et al (2003Raymond et al ( , 2005 and Khol-Parisini et al (2012), we observed no adverse effects between the different DON dosages in serum total protein, serum globulins and serum albumin (Tables 4 and 5). However, Johnson et al (1997) found a decrease in serum total protein, serum globulins and serum albumin concentrations in DON-exposed horses that may have been related to impaired liver metabolism.…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, none of the horses demonstrated any clinical signs commonly associated with the intake of DON such as colic or depression. Similar to our study, Johnson et al (1997) and Khol-Parisini et al (2012) also observed no adverse effects on the feed intake of horses fed DONcontaminated barley (36-44 mg DON/kg) or oats (20.2 mg DON/kg), which even exceeded the DON intake level applied in the Raymond et al (2003Raymond et al ( , 2005 studies and our own study.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Khol‐Parisini et al. () observed no adverse effects on general health in a cross‐over design the impact of DON on cellular and humoral immune effects in horses fed for 14 days naturally contaminated 2 kg oat diets with low (0.49 mg DON/kg diet) and high (20.2 mg DON/kg diet) levels, allowing for a 3‐week wash‐out. Serum haptoglobin concentration was significantly elevated at the high dose, but only minor effects were noted for differential blood counts and serum biochemistry, and no effects were seen for lymphocytes and their proliferation (concanavalin A, phytohaemagglutinin and pokeweed mitogen).…”
Section: Hazard Identification and Characterisationmentioning
confidence: 99%
“…Regarding the effect on cellular and humoral immune parameters in horses, an experiment using naturally DON contaminated grains (high contamination −20.2 mg/kg and low contamination −0.49 mg/kg) was conducted by Khol-Parisini et al [ 121 ] on two groups of five mares for two weeks. No adverse effects were observed; however, haptoglobin concentrations increased after feeding DON ( p = 0.04).…”
Section: Deoxynivalenolmentioning
confidence: 99%